Midterm Outcomes of Endovascular Repair of Aortic Arch Aneurysms with the Gore Thoracic Branch Endoprosthesis. (December 2022) - Liang, Nathan L.; Dake, Michael D.; Fischbein, Michael P.; Bavaria, Joseph E.; Desai, Nimesh D.; Oderich, Gustavo S.; Singh, Michael J.; Fillinger, Mark; Suckow, Bjoern D.; Matsumura, Jon S.; Patel, Himanshu J.; Makaroun, Michel S.
Abstract : Objective: Aortic aneurysms involving aortic arch vessels are anatomically unsuitable for standard thoracic endovascular repair (TEVAR) without cervical debranching of the arch vessels. Three year outcomes of a single branched thoracic endograft following previous publication of peri-operative and one year outcomes are reported. Methods: This was a multicentre feasibility trial of the GORE TAG Thoracic Branch Endoprosthesis (TBE), a thoracic endovascular graft incorporating a single retrograde branch for aortic arch vessel perfusion. The first study arm enrolled patients with an intact descending thoracic aortic aneurysm extending to the distal arch with left subclavian artery (LSA) incorporation (zone 2). The second arm enrolled patients with arch aneurysms requiring incorporation of the left carotid or innominate artery (zone 0/1) and extra-anatomic surgical revascularisation of the remaining aortic arch vessels. Outcomes at three years are reported. Results: The cohort comprised 40 patients (31 zone 2, nine zone 0/1). The majority were male (52%). Mean follow up was 1 408 ± 552 days in the zone 2 and 1 187 ± 766 days in the zone 0/1 cohort. During three year follow up there was no device migration, fracture, or aortic rupture in either arm. In the zone 2 arm, freedom from re-intervention was 97% at one and three years but there were two side branch occlusions. Two patients had aneurysm enlargement > 5 mm without documented endoleak or re-intervention. Freedom from death at one and three years was 90% and 84%. In the zone 0/1 arm there were no re-interventions, loss of branch patency, or aneurysm enlargement at three years. Cerebrovascular events occurred in three patients during follow up: two unrelated to the device or procedure, and one of unknown relationship. Two patients in this arm died during the follow up period, both unrelated to the procedure or the aneurysm. Conclusion: Initial three year results of the TBE device for endovascular repair of arch aneurysms show favourable patency and durability with low rates of graft related complications.